The concept of “woman” in the “tardofranquismo” (1960-1975): the NO-DO as an instrument for the control of female emancipation - Guichot Reina, Virginia (Historia y Memoria de la Educación, 2022)
The Plan de Estabilización y Liberalización Económica (1959) is considered the milestone that marks the beginning of a new stage of the Franco Regime called «technocratic developmentalism» (desarrollismo tecnocrático). Unique circumstances allowed a strong propulsion toward women´s emancipation, thanks to the greater inclusion of women in the labor force, a phenomenon that had been significantly hampered by the Franco dictatorship previously. In addition to other cultural considerations, these economic changes questioned the ideal of the «angel of the home» that Francoism had promoted for women. Consequently, the dictatorial regime employed its most effective propaganda, the newsreel NO-DO (Noticiarios y Documentales, News Programs and Documentaries), to safeguard this model. In this study we aim to discover the discursive strategies used by the NO-DO to discredit any women´s expectations that did not align with the official female stereotype of the Francoist Regime in the «technocratic developmentalism» (1960-1975). We have focused on reports that showed news linked to primary, secondary, and university education, as well as vocational training. The methodology employed in this research is that of Critical Discourse Analysis (CDA), applied to verbal and non-verbal discourse, joined to techniques of audiovisual analysis. Our results reveal that female models differing from traditional ones are discredited by means such as teasing, irony and, in general, derogatory language. Moreover, the presence of women in traditionally masculine spaces is omitted. At the same time, the «National-Catholic» archetype about women continues to be reinforced by verbal discourse and images. This period also saw a greater visualization of women in classrooms.